(untitled) (World Science, 2022)
Negligence in the use of human labor in demining dangerous areas can result in great human casualties. If we consider that we live in a modern information society, we can say that before the reconstruction and rehabilitation work in these areas, there is a need to apply information and communication technologies in the field of mine clearance to minimize human labor, hazards and losses. The scientific work presents the development of UAVs used for geo-detection of explosive surface mines by computer vision. The proposed integrated unmanned aerial vehicles will enable the acquisition of danger zones by spectral mapping and aim to clear explosives 100% and as soon as possible. In order to save time, it is important to identify the areas beyond the mine operations as well as detecting the mined areas. The proposed equipment will allow obtaining a map of the boundaries of dangerous areas. This will allow mines to be detected in larger areas and with minimal risks in the shortest possible time.